STRATEGI PENGEMBANGAN DAN PROMOSI DALAM MENARIK MINAT WISATAWAN PULAU KUMALA - Awang M. Rifani; Nada Selvia (Prodi Administrasi Negara FISIPOL Universitas Kutai Kartanegara, 2020)
Strategic Plan (Renstra 2016-2021), Kutai Kartanegara Regency Tourism Office in an effort to achieve goals and targets implemented through strategies and policies, in accordance with tasks and functions, based on strategic issues in the field of development. However, in its application, tourist attractions in Kutai Kartanegara Regency in general have not been fully developed optimally, this can be described through the author's initial observations, namely the lack of rides as a tourist attraction. The author uses the type of qualitative research